Kajian Potensi Dan Peluang Pembangunan Infrastruktur Di Sektor Sosial Dengan Skema KBPU - Irawan, Towaf Totok (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2016)
This study aims to formulate recommendations and opportunities for potential infrastructure development in the social sector by using KPBU scheme. The direct beneficiaries of this activity are the Deputy of Investment Planning as a unit that is directly responsible for formulating the proposed establishment of the Act related KPBU in the field of infrastructure investment. The output of this activity is also expected to be useful for investors in infrastructure and related stakeholders. Model cooperation Public Private Partnership in social infrastructure should take into account the uniqueness of each sector, particularly the constraints, risks and macro conditions, including fiscal policy and commitment to the objective of each sector. So that needs to be made cooperation mechanism Public Private Partnership in the field of social infrastructure by making adjustments to the conditions and limitations in the field of social infrastructure. Results and recommendations are discussed further in the paper. Keywords: Multi Criteria Analysis, infrastructure development